PELATIHAN PENGOLAHAN SATE KERANG SEBAGAI PRODUK FROOZEN FOOD BAGI MASYARAKAT SEKITAR MANGROVE DESA TONGKE-TONGKE SINJAI KECAMATAN SINJAI TIMUR - hasan, tahirah; Juhana, Juhana (Bina Bahari, 2022)
Tongke-tongke Village is one of the Mangrove Conservation Areas in the East Sinjai area. The condition of mangroves that grow in this area is in a dense category, and its distribution is more towards the sea and has become one of the natural tourist destinations in the area. The many types of shellfish that live in this area are a source of income for local residents, especially those around tourist areas. The purpose of this activity is to improve the skills of residents who live in the mangrove ecotourism area of Tongke-tongke village in making scallop satay which can be a special menu for culinary offerings for visitors and souvenirs from the area. The activity was attended by 20 participants consisting of mothers and teenagers, carried out using lecture methods and practical demonstrations. From the results of evaluation and monitoring at the end of the activity, it shows that this activity is enthusiastically sought after by coastal communities, as well as increasing the ability of the surrounding community to process the many shellfish in the area, into culinary offerings that are more durable and taste delicious.scallop satay; Tongke-tongke; frozen food; mangrove